The Teaching of International Law in Higher Institutions in the SADC Region - Maruma, Kholofelo (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This paper explores the epistemic and pedagogical considerations in the teaching of international law in Southern African Development Communities. It aims to address various aspects of teaching international law, including innovative teaching methods, integrating technology, the role of case studies and simulations, assessment, and evaluation, pedagogical challenges and opportunities, theoretical and practical perspectives, global perspectives, teaching in non-traditional settings, and the role of international law in multi-, inter-, and trans-disciplinary education. By examining these areas, the paper seeks to contribute to the advancement of effective and comprehensive approaches to teaching international law in higher education